2017
DOI: 10.1111/cote.12327
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sorption isotherms for colorants present in Dyers’ madder (Rubia tinctorum L.) provide new insights into historical dyeing

Abstract: Dyers madder (Rubia tinctorum L.) has been famously used throughout history as a source of red dye. The sorption onto mordanted wool of the major colorant components of R. tinctorum, alizarin and the glycosides ruberythric acid and lucidin primeveroside, is studied herein. Sorption of a purified 1:1 mixture of ruberythric acid:lucidin primeveroside most closely followed a Temkin isotherm (R 2 0.925), whereas alizarin followed a Freundlich isotherm (R 2 0.940). These results were compared with HPLC chromatogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Looking at weld compounds, the glucoside ldg has poor dye uptake, probably caused by a diminished bonding ability with the mordant. The poor uptake for the glycosides does not match results from Ford et al [21], wherein it was observed that ruberythric acid has preferential sorption properties on wool over the aglycone alizarin. In the case of glucoside ldg, one of two vicinal hydroxyl groups is attached to glucose and no longer available for bonding.…”
Section: Resultscontrasting
confidence: 78%
See 3 more Smart Citations
“…Looking at weld compounds, the glucoside ldg has poor dye uptake, probably caused by a diminished bonding ability with the mordant. The poor uptake for the glycosides does not match results from Ford et al [21], wherein it was observed that ruberythric acid has preferential sorption properties on wool over the aglycone alizarin. In the case of glucoside ldg, one of two vicinal hydroxyl groups is attached to glucose and no longer available for bonding.…”
Section: Resultscontrasting
confidence: 78%
“…The poor uptake for the glycosides does not match results from Ford et al . , wherein it was observed that ruberythric acid has preferential sorption properties on wool over the aglycone alizarin. Differences in experimental set‐up (dyeing time, concentration, liquor‐fibre ratio) may be a reason for this.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison between natural dyes and synthetic dyes, natural dyes are non-allergic, non-toxic, biodegradable, and do not cause environmental pollution [1, 2, 3, 4]. The use of madder (red dye) has been flourishing for centuries and ranging from Europe, Asia to Africa [5, 6, 7]. The dried roots of this plant are used as a component in herbal medicines for its anticancer, antifungal, anti-inflammatory and antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%